Measuring Financial Protection in Health - Wagstaff, Adam (World Bank, Washington, DC, 2012)
Health systems are not just about improving health: good ones also ensure that people are protected from the financial consequences of receiving medical care. Anecdotal evidence suggests health systems often perform badly in this respect, apparently with devastating consequences for households, especially poor ones and near-poor ones. Two principal methods have been used to measure financial protection in health. Both relate a household's out-of-pocket spending to a threshold defined in terms of living standards in the absence of the spending: the first defines spending as catastrophic if it exceeds a certain percentage of the living standards measure; the second defines spending as impoverishing if it makes the difference between a household being above and below the poverty line. The paper provides an overview of the methods and issues arising in each case, and presents empirical work in the area of financial protection in health, including the impacts of government policy. The paper also reviews a recent critique of the methods used to measure financial protection.